Delimitation and revision of the genus Thymbra (Lamiaceae) - Bräuchler, Christian (Phytotaxa, 2018)
The importance of comprehensive species sampling in phylogenetics and revisions of taxonomically complex groups is outlined using an example from Lamiaceae. To render the genus Thymbra into a well circumscribed, natural and monophyletic group, three species are transferred from Satureja to Thymbra. A run down of the classification history is provided along with an updated generic circumscription for Thymbra. Important diagnostic characters are discussed and a key to the species of Thymbra is presented. Notes on both types and distribution are provided for each species accompanied by illustration of representative herbarium specimens. Finally, Thymus cephalotos, a name currently placed in the synonymy of Thymbra capitata, is typified to fix its exclusion from Thymbra.